Sensory-Induced Human LTP-Like Synaptic Plasticity – Using Visual Evoked Potentials to Explore the Relation Between LTP-Like Synaptic Plasticity and Visual Perceptual Learning - Lengali, Lilly; Hippe, Johannes; Hatlestad-Hall, Christoffer; Rygvold, Trine Waage; Sneve, Markus Handal; Andersson, Stein (Frontiers in Human Neuroscience, 2021)
Objective: Stimulus-selective response modulation of sensory evoked potentials represents a well-established non-invasive index of long-term potentiation-like (LTP-like) synaptic plasticity in the human sensory cortices. Although our understanding of the mechanisms underlying stimulus-selective response modulation has increased over the past two decades, it remains unclear how this form of LTP-like synaptic plasticity is related to other basic learning mechanisms, such as perceptual learning. The aim of the current study was twofold; firstly, we aimed to corroborate former stimulus-selective response modulation studies, demonstrating modulation of visual evoked potential components following high-frequency visual stimulation. Secondly, we aimed to investigate the association between the magnitudes of LTP-like plasticity and visual perceptual learning. Methods: 42 healthy adults participated in the study. EEG data was recorded during a standard high-frequency stimulus-selective response modulation paradigm. Amplitude values were measured from the peaks of visual components C1, P1, and N1. Embedded in the same experimental session, the visual perceptual learning task required the participants to discriminate between a masked checkerboard pattern and a visual “noise” stimulus before, during and after the stimulus-selective response modulation probes. Results: We demonstrated significant amplitude modulations of visual evoked potentials components C1 and N1 from baseline to both post-stimulation probes. In the visual perceptual learning task, we observed a significant change in the average threshold levels from the first to the second round. No significant association between the magnitudes of LTP-like plasticity and performance on the visual perceptual learning task was evident. Conclusions: To the extent of our knowledge, this study is the first to examine the relationship between the visual stimulus-selective response modulation phenomenon and visual perceptual learning in humans. In accordance with previous studies, we demonstrated robust amplitude modulations of the C1 and N1 components of the visual evoked potential waveform. However, we did not observe any significant correlations between modulation magnitude of visual evoked potential components and visual perceptual learning task performance, suggesting that these phenomena rely on separate learning mechanisms implemented by different neural mechanisms.